12.2k views
5 votes
28. What is the solution to 12-(2x+6) = -4x +10 +2(x-8) *

A. no solution
B. infinite solutions
C. x= 6
D. x= - 6

Question 28 Explanation *

2 Answers

7 votes

Answer:

The solution to the expression is: No Solution

Explanation:

PEMDAS

12 - (2x + 6) = - 4x + 10 + 2 (x - 8)

12 - 2x - 6 = - 4x + 10 + 2x - 16

-2x + 12 - 6 = - 4x + 2x + 10 - 16

Transfer like terms to each side, [x] on one side, and the numbers with it, [x], on the other.

- 2x + 6 = - 2x - 6

+ 2x -6 -6

0 = -12

Since there is no x for the solution, there is no solution.

Hope this helped!

User DSchultz
by
5.3k points
5 votes

Answer:

A-no solution

Explanation:

There are no values of x that make the equation true.

User Okeydoke
by
4.5k points